2009
DOI: 10.2337/dc09-0191
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C, Albuminuria, and Mortality Among Older Adults With Diabetes

Abstract: OBJECTIVEAlbuminuria and impaired glomerular filtration rate (GFR) are each associated with poor health outcomes among individuals with diabetes. Joint associations of albuminuria and impaired GFR with mortality have not been comprehensively evaluated in this population.RESEARCH DESIGN AND METHODSThis is a cohort study among Cardiovascular Health Study participants with diabetes, mean age 78 years. GFR was estimated using serum cystatin C and serum creatinine. Albumin-to-creatinine ratio (ACR) was measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 23 publications
3
88
0
Order By: Relevance
“…Higher levels of albuminuria have been reported to be associated with increased mortality in prior studies of older adults with diabetes mellitus and in the general population (11,20). O'Hare and colleagues reported ACR levels Ն30 mg/g to be associated with increased mortality, regardless of age, among U.S. veterans with diabetes mellitus (11).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of albuminuria have been reported to be associated with increased mortality in prior studies of older adults with diabetes mellitus and in the general population (11,20). O'Hare and colleagues reported ACR levels Ն30 mg/g to be associated with increased mortality, regardless of age, among U.S. veterans with diabetes mellitus (11).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 It was shown that serum cystatin C is superior for prediction of mortality and cardiovascular events among elderly and among elderly diabetic patients compared to serum creatinine or estimated GFR based on creatinine. 26,27 In the past years, also equations based on both creatinine and cystatin C were developed, widely accepted is the CKD-EPI creatinine/cystatin equation. 28 It was also shown that serum cystatin C is a strong predictor of death in patients suffering from stroke, but there are no data about predicting long-term mortality in these patients comparing serum cystatin C and estimated GFR based on creatinine or creatinine and cystatin C. 29 The aim of our study was to compare the associations of serum creatinine, estimated GFR (CKD-EPI creatinine and CKD-EPI creatinine/cystatin equations), serum cystatin C and long-term mortality risk in patients suffering from ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…CysC is supported by additional studies to be a good early predictor of acute kidney injury [15]. It has already been reported that CysC is linked to the mortality rate of patients with heart failure, regardless of objective renal function [16], and that it yields a higher rate of accuracy than serum Cr in predicting the mortality rate of diabetic patients [17].…”
Section: Introductionmentioning
confidence: 54%